MEAN MONTHLY WATER BALANCE IN NEUQUÉN, ARGENTINA - Marisa Gloria Cogliati; Griselda Ostertag; Matías Caso; Florencia Gisella Finessi; Damián Groch (Boletín Geográfico)
In recent years there has been an increase in the average temperature in different regions, which is associated with an increase in evapotranspiration, causing greater deficit and water stress in areas with arid climates. The climate of the Province of Neuquén presents a marked gradient of precipitations west-east, in areas near the mountain range of the Andes stand out cold winters with rains and snowfalls, and summers drier and more temperate; to the east, precipitation decreases, presenting a semi-desert environment identified with the Patagonian steppe. The knowledge of the evolution of the different components of the water balance in arid zones is of fundamental importance for the estimation of the coverage of the hydric requirements of the vegetation, and of the different productive activities that are developed in the area; as well as for the control of the state of the wetlands (mallines). In this work, the spatial variations of the moisture balance components are presented in detail from information from the network of surface meteorological stations in the province of Neuquén